Major drivers to determine the native or exotic nature of the fish assemblage in the European southern tip. - Ramon José De Miguel; Lucía Isabel Gálvez-Bravo (Frontiers in Marine Science, 2015)
Following the recommendations of the Water Framework Directive (WFD) in the European Union, research on the current fish community status from the Guadalquivir River basin was addressed. Among the large quantity of information registered, this study was focused on the environmental variables that mainly influenced the presence of native or exotic species in the fish assemblages. A representative sampling of the whole Guadalquivir River network was carried throughout 1037 sites during four years (2006-2009), collecting data from both habitat and fish assemblages. The formers, including site and catchment scale variables, were registered in situ or ex situ using Geographical Information Systems, while for fish assemblages, electrofishing was the sampling gear used. Canonical Correspondence Analysis (CCA) was performed in order to find the axes that best separated the fish assemblages with exotic species from those with natives. The first and second axes in the CCA accounted for 68% and 56% of the fish assemblage group’s ordination, respectively. When using species as predictors, mostly native species were located in the negative side of the first axis, whereas mainly exotic species were in the positive side. Furthermore, whether environmental variables were used as predictors, the negative side of the first axis placed less anthropogenic land uses and more altitude, while the positive side located predictors related to wider downstream reaches more affected by human disturbances. According to other results from different watersheds in Southern Europe, exotic species were mainly located in downstream reaches under the influence of reservoirs. On the other hand native species preferred stretches in areas with less anthropic land uses upstream from reservoirs.